PTU-217 Hypervirulent clostridium difficile has a unique odour profile. (22nd June 2015) - Reade, S; Simpson, H; Aggio, RBM; Probert, CSJ
Abstract : Introduction: C. difficile is a spore-forming bacterium that causes infectious diarrhoea, having a characteristic odour. Symptoms range from a mild disturbance to severe illness with ulceration and bleeding from the colon and perforation of the intestine. Patients treated with broad spectrum antibiotics are at the greatest risk of contracting C. difficile infection. Problematic ribotypes have been defined. PCR-based tests depend on a prior knowledge of the gene sequences of strains being detected and thus new or different strains may be missed. A test that is dependent on metabolic volatile organic compounds (VOCs) would be free from such constraints. Method: Briefly, 4 C. difficile strains, separated by their genotype and toxin expression (toxins: A, B or binary), were cultured on fastidious anaerobe (FA) agar and later in FA broth cultures. Headspace gases were collected using a CAR/PDMS/DVB SPME fibre before GC-MS analysis. Chromatograms were analysed and data was processed in-house using AMDIS and Metab. A one-way ANOVA followed by Tukey with Bonferroni multiple comparison correction were performed ( p < 0.001). Results: Conclusion: Combinations of VOCs were found to be characteristic to each of the four ribotypes. These results point to potential indicators of different metabolic pathways in virulent (108536/027) and less-virulent strains. The pipeline of analysis used in this study has enabled the chemical identification of VOCs, providing an insight into the underlying metabolic pathways that are active during bacterial growth. Rapid detection of VOCs emitted from the HS of C. difficile may have the utility as a non-invasive diagnostic test. Disclosure of interest: None Declared.